2020
DOI: 10.1186/s12937-020-00589-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake in lactating mothers in China 2018: report of a survey

Abstract: Background: The nutritional status of lactating mothers (LMs) is related to their own health and significantly impacts the secretion of breast-milk, and subsequently the growth and development of infants. Due to the influence of regional economy, traditional habits, and lack of nutrition knowledge, the problem of poor dietary nutrition among Chinese LMs is prominent. We aimed to evaluate and compare the dietary and nutrient intakes in LMs from urban and rural areas in China to provide baseline data for the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 27 publications
(56 reference statements)
7
25
4
Order By: Relevance
“…Among them, 86.4% had a lower vitamin A intake than the RNI value [ 7 ]. However, our previous studies on urban and rural areas in 13 provinces and municipalities showed that more than 90% of Chinese lactating mothers had lower dietary vitamin A intake than the RNI value in 2018 [ 5 ]. The reasons for this difference may be the inconsistency of dietary survey methods, the limited dietary sources of vitamin A, and the influence of geography, customs, and economic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 86.4% had a lower vitamin A intake than the RNI value [ 7 ]. However, our previous studies on urban and rural areas in 13 provinces and municipalities showed that more than 90% of Chinese lactating mothers had lower dietary vitamin A intake than the RNI value in 2018 [ 5 ]. The reasons for this difference may be the inconsistency of dietary survey methods, the limited dietary sources of vitamin A, and the influence of geography, customs, and economic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Chinese Nutrition Society established new dietary guidelines in 2016, which emphasise increasing the intake of vitamin A-rich foods to improve the nutritional status of lactating mothers [ 4 ], a dietary survey of Chinese lactating mothers completed by our research group in 2018 showed that the dietary vitamin A intake of this population is still lower than the recommended value, especially in rural areas [ 5 ]. There are two dietary forms of vitamin A. Preformed vitamin A (retinol and retinyl ester) is derived from animal sources such as animal liver, meat, dairy products, and fish.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 86.4% of participants had lower vitamin A intake than the RNI value [7]. However, our previous studies on urban and rural areas in 13 provinces and municipalities showed that more than 90% of Chinese lactating mothers had lower dietary vitamin A intake than the RNI value in 2018 [5]. The reasons for this difference may be the inconsistency of dietary survey methods, the limited dietary sources of vitamin A, the in uence of geography, customs and economic conditions, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Chinese Nutrition Society has established new dietary guidelines in 2016, which emphasizes increasing the intake of vitamin A rich foods to improve the nutritional status of lactating mothers [4], the dietary survey of Chinese lactating mothers completed by our research group in 2018 showed that the dietary vitamin A intake of this population is still lower than the recommended value, especially in rural areas [5]. The dietary source of vitamin A is limited, mainly animal liver and dark-green leafy vegetables and fruits.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Insufficient vitamin A (VA) intake leads to VA deficiency. 10 As a fat-soluble vitamin, VA plays a key role in many physiological functions, including vision, growth, reproduction, hematopoiesis, and immunity. 11 Research has shown that VA is essential to maintain the function of the meibomian gland, and VA supplementation benefits eye-surface health.…”
Section: Introductionmentioning
confidence: 99%